Effect of girls’ education on cancer awareness and screening in a natural experiment in Lesotho - Liao, Janny; Moshoeshoe, Ramaele; Holmes, Michelle D.; Subramanian, S. V.; De Neve, Jan-Walter (Nature Communications, 2025)
Breast and cervical cancers are important causes of disability and premature death among women in Sub-Saharan Africa. Previous research has linked girls’ education to cancer service access. Here, we examine the causal effect of girls’ educational attainment on cancer screening practices by means of a natural experiment in Lesotho. In particular, we exploit variation in educational attainment among women that was introduced by an educational policy (a school-entry age cut-off). Data on awareness towards breast cancer, knowledge of Pap smear, breast self-exam, breast clinical exam, and having received a Pap smear is extracted from the Lesotho Demographic and Health Surveys 2009-10 and 2014 (N = 7971). Each additional year of schooling caused by the education policy increases awareness of breast cancer by 4.7 percentage points (p = 0.014, 95% Confidence Interval [CI]: 1.0, 8.5), awareness of Pap smear by 5.9 percentage points (p = 0.001, 95% CI: 2.3, 9.5), and engagement in Pap smear by 3.5 percentage points (p = 0.004, 95% CI: 1.1, 5.8). We found no statistically significant effects on breast self-exam and breast clinical exam.
Online veröffentlicht: 20. April 2025
Gesehen am 06.10.2025